Pengembangan Buku Saku Kesehatan sebagai Media Edukasi pada Pasien COVID-19 yang Menjalani Isolasi Mandiri - Lolita Lolita; Azis Ikhsanudin; Yuniar Nabilla Ligawa; Nidaul Makwa; Febrilla Ayu Larasati; Rachmawati Sukmaningtyas; Nabila Nabila; Asiilah Fatihatul Khoirot; Putri Hanisari; Faril Gunanti; Merry Ramdhani (Universitas Muhammadiyah Semarang, 2023)
Coronavirus Illness (COVID)-19, an infectious respiratory illness were first dicscovered in Wuhan, China in 2019. This diseases has become a global pandemic which spread quiclkly worldwide. In order to combat this pandemic, it is critical that health efforts must be carried out by all segments of society. Health education is one of the health initiatives, particularly for COVID-19 patients who are experiencing self-isolation. The availability of COVID-19 health education pocket books may help them in better understanding about COVID-19. The method of health education is to provide a pocket book named